Health worker in primary health care: the nurse’s perspective - Evangelista, Anne Itamara Benigna; Pontes, Andrezza Graziella Veríssimo; Silva, Jennifer do Vale e; Saraiva, Ana Karinne de Moura (Rev Rene, 2011)
This is a qualitative research with the goal of describing the experiences lived by primary care nurses concerning workers’ health. Semi structured interviews were held with nurses of the Family Health Strategy in Mossoró, Brazil, between October and December 2010. From the thematic analysis it was revealed: actions on worker’s health based on the models of occupational medicine and Occupational health; difficulties concerning the reporting of work accidents, work of family health Strategy, worker’s life, logic of companies productivity and nursing education as well as the existence of Reference Centers in Occupational Health and the desire of workers to learn how to overcome difficult situations. To consolidate the health of worker in primary health care seems to be the co-responsibility of management, education and health services to review conceptions and practices about the relationship between work and health.